2023
DOI: 10.5772/intechopen.111778
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Attributes in Aspergillus fumigatus

Abstract: Aspergillus fumigatus is one of the most important opportunistic fungal pathogens. It causes various types of infections in humans, from skin, lung, and allergic infections to invasive infections. However, these stand out because their mortality rate can reach up to 95%. A. fumigatus is a ubiquitous fungus and, therefore, humans are in constant contact with it without major risk, except when there is a predisposing factor on the host, that allows the fungus to penetrate and invade the tissues. It is fascinatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 101 publications
0
1
0
Order By: Relevance
“…Its functions are to inhibit the phagocytic activity of macrophages, reduce the cytotoxic activity of T-cells, and prevent the induction of apoptosis in host cells. Additionally, studies have shown a positive correlation between GT production and the pathogenicity of A. fumigatus [33]. None of the Aspergillus isolates produced aflatoxins.…”
Section: Resultsmentioning
confidence: 95%
“…Its functions are to inhibit the phagocytic activity of macrophages, reduce the cytotoxic activity of T-cells, and prevent the induction of apoptosis in host cells. Additionally, studies have shown a positive correlation between GT production and the pathogenicity of A. fumigatus [33]. None of the Aspergillus isolates produced aflatoxins.…”
Section: Resultsmentioning
confidence: 95%